Linguistik Modern Persepektif Doktor Mahmud Fahmi Al-Hijazi - Humaidi Humaidi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2020)
Abstract Linguistics is the study of language scientifically. In his study, linguistics has the scope of studies and methods of study. The scope of linguistic studies is phonology, morphology, syntax and semantics. Phonology research is the study of language sounds. Morphology is the field of linguistics that studies about word formation and morphemes in a language. Syntax is the study of the structure of language. And the last semantics is the study of meaning. While the methodology of linguistic studies are comparative linguistics, descriptive linguistics, historical linguistics, and contrastive linguistics.